Effects of applying sports liniment with massage on muscular relative strength of hip flexion and knee extension among male Muay Thai athletes: a randomised control trial - Johnson , Lee David; Sarinukul, Chawin; Rittirod, Theera; Konharn, Kurusart (Revista de Artes Marciales Asiáticas, 2024)
Background: Muay Thai, Thailand’s national sport, widely practiced globally, is known for using sports liniment before training and fights. A popular product is ‘Namman Muay’, an iconic symbol of Thailand, though its direct impact on performance lacks research. Objectives: Investigate the impact of Namman Muay on the rectus femoris of the dominant leg. Focus on muscular strength exercises – seated hip flexion and supine knee extension – with relative strength as the primary outcome. Material and Methods: A randomised control trial with 24 male Muay Thai fighters, divided into 12 in the Baby Oil (BO) and 12 in the Namman Muay (NM) group. Both groups received effleurage massage on the dominant kicking legs, followed by a RAMP warm-up. Performance measurements using Lafayette Handheld Dynamometer evaluated two isometric strength tests. Results: NM intervention showed significant increases in hip flexion and knee extension strength. Within groups, a 3% decrease was seen in the BO and an 11.6% increase in NM for hip flexion strength, and 1% decrease in BO and 6.9% increase in NM for knee extension strength. Conclusion: This study provides valuable insight to Muay Thai fighters and trainers, showing that 5 ml NM boosts relative muscular strength of hip flexion and knee extension. This could improve male Muay Thai fighters’ performance particularly when using kicking techniques.